Corporate Sector Restructuring : The Role of Government in Times of Crisis - Stone, Mark (Economic Issues; Economic Issues ;, 2003)
Examines the steps involved in restructuring the corporate sector. Large-scale corporate restructuring made necessary by a financial crisis is one of the most daunting challenges faced by economic policymakers. The government is forced to take a leading role, even if indirectly, because of the need to prioritize policy goals, address market failures, reform the legal and tax systems, and deal with the resistance of powerful interest groups.